2003
DOI: 10.1046/j.1468-1331.2003.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide as a vasodilatory stimulus in cerebrovascular diseases and in conditions affecting the cerebral vasculature

Abstract: Pathologic processes affecting the brain vessels may damage cerebral vasodilatory capacity. Early detection of cerebral dysfunction plays an important role in the prevention of cerebrovascular diseases. In recent decades acetazolamide (AZ) has frequently been used for this purpose. In the present work the mechanism of action and the previous studies are reviewed. The authors conclude that AZ tests are useful in cerebrovascular research. Further investigations are recommended to prove how impaired reserve capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 130 publications
(234 reference statements)
7
97
1
Order By: Relevance
“…In fact, recent studies have shown that the CVR is a reliable predictor of subsequent ischemic stroke; thus, an evaluation of the CVR should be important for considering the therapeutic strategy for ischemic disease, including surgical intervention. 19 Indeed, in Moyamoya disease, the CVR is usually measured to determine whether revascularization surgery is necessary and which cerebral hemisphere should undergo surgery initially. 8,20,21 However, any measurement of CVR requires 2 SPECT evaluations, including resting and ACZ activation studies, which may be burdensome to patients, and ACZ activation may cause side effects such as headache and a feeling of discomfort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, recent studies have shown that the CVR is a reliable predictor of subsequent ischemic stroke; thus, an evaluation of the CVR should be important for considering the therapeutic strategy for ischemic disease, including surgical intervention. 19 Indeed, in Moyamoya disease, the CVR is usually measured to determine whether revascularization surgery is necessary and which cerebral hemisphere should undergo surgery initially. 8,20,21 However, any measurement of CVR requires 2 SPECT evaluations, including resting and ACZ activation studies, which may be burdensome to patients, and ACZ activation may cause side effects such as headache and a feeling of discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…8,20,21 However, any measurement of CVR requires 2 SPECT evaluations, including resting and ACZ activation studies, which may be burdensome to patients, and ACZ activation may cause side effects such as headache and a feeling of discomfort. 19,22 Especially in patients with a very severe decrease in CVR, the administration of ACZ sometimes causes a further reduction in CBF due to the vascular steal phenomenon to the adjacent area with relatively preserved CVR. 19,22 Therefore, ACZ should be administered cautiously in patients with severe ischemic symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AZ inhibits the activity of carbonic anhydrase, which reversibly catalyses the formation of H 2 CO 3 from CO 2 + H 2 O. It increases the concentrations of H + and CO 2 , which is assumed to be the stimuli for the increase in flow; however, the exact mechanism is yet to be determined (Settakis et al, 2003).…”
Section: Independent Regulation Of Neurovascular Coupling and Acetazomentioning
confidence: 99%
“…The SPECT study was started after 60 min. For the stimulation study, the radiopharmaceutical was injected 15 min after acetazolamide (15 mg of diamox per kilogram; Lederle Laboratories) because earlier studies showed maximal vasodilation at this time (13).…”
Section: Methodsmentioning
confidence: 99%